How to Write an Abstract of a Research Project - Elaine J. Rabin (Association of American Medical Colleges, 2012)
Abstract This resource is a short manual to guide scholars in writing abstract of a research project to submit for presentation or publication in medicine and related fields. Appendices supply sample abstracts for various study designs and published guidelines for specific types of abstracts. This is not meant to be a comprehensive manual for designing and performing a study or analyzing data; it assumes that these steps have been completed. This manual was created because residents in our department were not consistently developing the ability to write a publishable abstract over the course of their residency despite some individual mentorship, a structured research curriculum, and the availability of numerous examples in scholarly journals. A search of available guides to writing abstracts illuminated the need for a single guide with sufficient detail, examples, and advice on avoiding common mistakes which was also generalizable across medical and related fields. This prompted the development of this guide based on previous guides and the author's experience as a researcher and research mentor. Using this manual as a reference when creating abstracts improved the abstracts produced by residents, as well as residents' ability to clarify the objectives of their projects.